Ação de anticoagulantes na atividade enzimática de proteases e carboidrases do intestino médio de Lutzomyia longipalpis (Diptera: Psychodidae) e Aedes aegypti (Diptera: Culicidae) - Tarcísio de Freitas Milagres (2019)
Leishmaniasis is a complex of diseases caused by protozoan parasites of the genus Leishmania, being transmitted to their vertebrate hosts by minute insects called sand flies. Leishmania infantum, the etiologic agent of visceral leishmaniasis in the Americas, is transmitted to vertebrate hosts in the New World through the bites of Lutzomyia longipalpis (Diptera, Psychodidae) females. Aedes aegypti, a mosquito species belonging to the order Diptera, family Culicidae, is a cosmopolitan species that is extremely adapted to urban and domestic environments, being the urban vector of arboviruses such as Dengue, Chikungunya, Zika and yellow fever. For a better understanding of the digestive physiology of insect vectors, artificial feeds containing drugs that can manipulate their digestive physiology are commonly used. Once blood is withdrawn from the vertebrate host and administered via an artificial feed, the addition of anticoagulants is crucial. The present study tries to understand the possible interference that anticoagulants may have on intestinal protease and glycosidase activities of two vectors of high importance in the transmission of protozoans and arboviruses to humans: L. longipalpis and A. aegypti. The intestinal activity of α-glucosidase, aminopeptidase, trypsin, and N-acetyl-β-Dhexosaminidase enzymes were evaluated in the presence of heparin at concentrations of 2U and 150U/mL, sodium citrate, and EDTA. We observed that the use of 2U/mL heparin in an artificial blood feed to L. longipalpis resulted in an a more uniform α-glycosidase activity profile activity, suggesting that heparin is the anticoagulant of choice to study αglycosidase activity in L. longipalpis. EDTA seems to be the best anticoagulant choice to study A. aegypti intestinal α-glycosidase activity as the enzymatic profile observed for this coagulant resembles the profile observed for insects fed on a human host. Sodium citrate and heparin (2U / mL) are the anticoagulants of choice for the study of intestinal hexosaminidase activity of L. longipalpis. Regarding intestinal hexosaminidase activity of female A. aegypti, the choice of an anticoagulant seems to have no influence on the enzymatic activity. Heparin (2U / mL) is the anticoagulant of choice for the study of intestinal aminopeptidase activity of L. longipalpis and A. aegypti. The choice of anticoagulant had a great impact on the L. longipalpis intestinal trypsinolytic activity, with heparin (at the concentrations of 2U/mL and 150U/mL) being the anticoagulant of choice for the study of trypsin activity in this phlebotomine species. We have also seen that sodium citrate and EDTA are the anticoagulants of choice for the study of A. aegypti intestinal trypsinolytic activity. We conclude that the correct choice of an anticoagulant during artificial feeds is crucial for the study of intestinal protease activity in haematophagous insects. The wrong choice of an anticoagulant could mask the results and have a direct influence on the intestinal physiology of these insects or in experiments investigating vector-pathogen interaction within the gut of haematophagous arthropods.